Living labs for public sector innovation: An integrative literature review - Lars Fuglsang; Anne Vorre Hansen; Ines Mergel; Maria Taivalsaari Røhnebæk (Administrative Sciences, 2021)
The public administration literature and adjacent fields have devoted increasing attention to living labs as environments and structures enabling the co-creation of public sector innovation. However, living labs remain a somewhat elusive concept and phenomenon, and there is a lack of understanding of its versatile nature. To gain a deeper understanding of the multiple dimensions of living labs, this article provides a review assessing how the environments, methods and outcomes of living labs are addressed in the extant research literature. The findings are drawn together in a model synthesizing how living labs link to public sector innovation, followed by an outline of knowledge gaps and future research avenues.
Keywords: 350; co-creation; living labs; public innovation; public value creation